La loi française du 11 juillet 1979 relative à la motivation des actes administratifs - Péquignot, Georges (Les Cahiers de droit, 1980)
This paper summarizes the changes brought about in French administrative law by a law of 1979 imposing on administrative authorities a broad duty to give reasons for their decisions. Traditionally, the state of the law had been that, failing a specific statutory requirement, administrative authorities were under no obligation to provide reasons. This, however, had not prevented the Conseil d'État from reviewing administrative action — even of a clearly discretionary nature — for unlawfulness or impropriety of motives. The new law is aimed at improving communications between administrative authorities and the public. It reverses the former rule for three broad classes of decisions concerning individual cases : those having an unfavourable effect on rights and interests, those allowing for more favourable treatment than is provided under a rule of general application, and those made by social security and unemployment assistance agencies. Alleviation or disregard of the new rule is allowed in cases of emergency, where confidentiality or secrecy is required by law, or where, no decision being made in a prescribed time, a negative decision is deemed to have been rendered. Guidelines for the implementation of the new law have been issued by the Prime Minister to all Ministers; the latter have in turn issued more detailed instructions to decision-making officers in their departments. Further guidance will have to come from the administrative courts when they are called upon to review decisions for insufficiency or impropriety of reasons. Ultimately, however, achievement of the goal of improving the quality of intercourse between citizens and administrative authorities will require the development of a more open and trustful relationship between them.